THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON FINANCIAL PERFORMANCE AT PTPN 1 LANGSA CITY - Nasrul Kahfi Lubis (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This research aims to find out the influence of leadership style and work motivation on financial performance at PTPN 1 Kota Langsa.  The sample used amounted to 84 respondents. The data analysis methods used are multiple linear regression analysis, and hypothesis proof using t test, F test, and determination coefficient analysis. Multiple linear regression analysis results obtained Y = 1.549 + 0.191X1 + 0.258X2. Adjusted R Square value is 0.664 or when percentage is 66.4%. This shows the variable leadership style and work motivation affects the financial performance at PTPN 1 Langsa City by 66.4%, while the rest by 33.6% (100% - 66.4%) influenced by other variables not studied in this study. T test results obtained that the variable leadership style and work motivation significantly affect the financial performance of PTPN I Langsa City. F test results obtained leadership style and work motivation significantly affect the financial performance of PTPN I Langsa City.